Պարսկական ճարտարապետության գոհարներից մեկը՝ Երևանում - Տեր-Մինասյան, Անուշ (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The Blue Mosque plays an important role in understanding the history of Yerevan, the artistic image of the city in that period, as well as in the comparative study with other monuments of Iranian architecture have the best and most complete picture of this architecture. It is also important to recognize the role of the Blue Mosque complex in the cultural life of Yerevan, both past and present. Today it is actively included in the cultural life of Yerevan, making it an important place for the manifestation and establishment of Armenian-Iranian cultural ties. In addition, the example of the restoration project of the Blue Mosque of Yerevan played a very important role in the cultural cooperation of the two countries and contributed to the appreciation, study, preservation, restoration, use and other issues of solving and implementing many architectural monuments within their borders.
Keywords: Ճարտարապետություն; Պարսկաստան